1985
DOI: 10.1093/geronj/40.3.296
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc, Copper, and Selenium Status of a Selected Sample of Canadian Elderly Women

Abstract: The zinc, copper, and selenium status of 90 noninstitutionalized Canadian elderly women (M age = 70.3 years) in a university community and consuming self-selected diets was assessed using hair and serum trace element levels and dietary trace element intakes. Mean (+/- SD) serum zinc and copper levels (analyzed via atomic absorption spectrophotometry, AA) were 1.09 +/- 0.13 and 1.22 +/- 0.29 micrograms/ml, respectively. Mean serum selenium (+/- SD) (analyzed via instrumental neutron activation analysis (INAA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In the present study, the mean serum Se level was 111.37 μg/L (SD = 22.32) which is similar to the level reported for other Asian countries such as Taiwan (110.9 μg/L) [ 44 ] and Japan (117.4 μg/L) [ 45 ], as well as Canada (115 μg/L) [ 46 ]. However, our Se values are generally lower than those obtained in the US during the National Health and Nutrition Examination Surveys (NHANES) of 2003–2004 (136.7 μg/L) [ 47 ].…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the mean serum Se level was 111.37 μg/L (SD = 22.32) which is similar to the level reported for other Asian countries such as Taiwan (110.9 μg/L) [ 44 ] and Japan (117.4 μg/L) [ 45 ], as well as Canada (115 μg/L) [ 46 ]. However, our Se values are generally lower than those obtained in the US during the National Health and Nutrition Examination Surveys (NHANES) of 2003–2004 (136.7 μg/L) [ 47 ].…”
Section: Discussionsupporting
confidence: 87%
“…It has been hypothesized that a reduction of selenium levels with age is linked to modified food habits. Moreover it has been demonstrated that, due to the great variation of food Se content, a dietary assessment of selenium is not reliable in an epidemiological study 48 , 49 . Modified food habits can, perhaps, explain differences between the elderly and other adults, but it does not seem plausible that it can explain the progressive decrease observed with age.…”
Section: Discussionmentioning
confidence: 99%
“…The effects appear to be cumulative, but it has been suggested that the role of nutrition is more important than age in the elderly population (1). Of all the nutrients involved in immunocompetence, selenium and zinc are the two trace elements that have been most frequently investigated in older adults (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Selenium's role in immune function, as well as cancer prevention, is related to its physiologic requirement as an active component in various enzymes involved in redox reactions protecting membranes from oxidative damage (14,15).…”
mentioning
confidence: 99%